Youth ministry: Offering hope in a COVID-19 South Africa through community - Aziz, Garth (HTS teologiese studies, 2021)
The president of the Republic of South Africa has addressed the nation many times during the coronavirus disease 2019 (COVID-19) restrictions and lockdown of 2020, and has spoken very strongly about and against the violence toward the vulnerable in our society. Whilst the COVID-19 pandemic has affected many societies, it has mainly revealed the brokenness in our society and the violence against the vulnerable on multiple levels. Arguably, a place where we can discover God is in the midst of our challenges and struggles, a place where God reveals plans and hopes for our lives. It, therefore, is in a place of hopelessness that wholeness can be discovered. This process, whilst painful, can also be transformative and even healing. This pandemic has created a context that has revealed brokenness in lives, systems and economics.Contribution: This article will look at how the church through its youth ministry can offer hope, specifically for the youth, as a vulnerable group, so that they may experience the transforming power of God amidst a global crisis through the creation of an alternative community.